Between seeing and not seeing : lo spazio intermedio di Stanley Kubrick - Tagliagambe, Silvano (Scenari, 2021)
his essay proposes a parallelism between Derrida’s philosophical thought and Kubrick’s cinematographic work concerning, in particular, the relationship between visible and invisible, between seeing and not seeing. In his work Memoirs of the blind, Jacques Derrida explores issues of vision, blindness, self-representation. In his opinion drawing is itself blind; as an act rooted in memory and anticipation, drawing necessarily replaces one kind of seeing (direct) with another (mediated). For Derrida the finger-eye guided by the mind and by the memory that provides insight: every self-portrait is a memoir, reflecting the “story,” the “history” that was, is, and will be. Kubrick was a true master of the medium of film and treated it as an art form, something which reveals to us fundamental aspects of the human condition: in his opinion this condition is such that we can only perceive the world through our senses. These perceptions pass through our brains and are “theory soaked” with our own views, assumptions, concepts, prejudices and desires in order to make any kind of sense or meaning of them. This theory soaking process involves attaching our fantasies to these perceptions. Fantasy therefore is a necessary part of interpreting the world and this means, for the subject at least, that the perceived world is never really free from fantasy and separating this from objective reality is an extraordinarily hard process. Indeed, at the extreme, it is impossible.